2022
DOI: 10.1021/acs.est.2c01087
|View full text |Cite
|
Sign up to set email alerts
|

Air Pollutant Emission Inventory of Waste-to-Energy Plants in China and Prediction by the Artificial Neural Network Approach

Abstract: The waste-to-energy (WTE) plant has been deployed in 205 cities in China. However, it always faces public resistance to be built because of the great concerns on flue gas pollutants (FGPs). There are limited studies on the socioeconomic heterogeneity analysis and prediction models of WTE capacity/ FGP emission inventories (EIs) based on big data. In this study, the incinerator level emission factors (EFs) in 2020 of PM, SO2, NO x , CO, HCl, dioxins, Hg, Cd + Tl, and Sb + As+ Pb + Cr + Co + Cu + Mn + Ni were ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 36 publications
(41 reference statements)
0
7
0
Order By: Relevance
“…Themelis 4 HCl, PM, dioxin, and heavy metals (Hg, Cd+TI, Sb+As+Pb+Cr+Co+Cu+Mn+Ni). Furthermore, previous studies examined the driving factors of MSW generation in China 12 , the relationships between incineration amounts and factors such as economic size and population density at the provincial level 13 and the correlation between socioeconomic factors and city-level emission factors 11 . However, factors governing the emission trends of multiple air pollutants from the WTE industry after the introduction of the 2014 emission standard remain unclear.…”
Section: Growth Of the Wte Industry In China And Environmental Perfor...mentioning
confidence: 99%
See 3 more Smart Citations
“…Themelis 4 HCl, PM, dioxin, and heavy metals (Hg, Cd+TI, Sb+As+Pb+Cr+Co+Cu+Mn+Ni). Furthermore, previous studies examined the driving factors of MSW generation in China 12 , the relationships between incineration amounts and factors such as economic size and population density at the provincial level 13 and the correlation between socioeconomic factors and city-level emission factors 11 . However, factors governing the emission trends of multiple air pollutants from the WTE industry after the introduction of the 2014 emission standard remain unclear.…”
Section: Growth Of the Wte Industry In China And Environmental Perfor...mentioning
confidence: 99%
“…In contrast to NOx, SO2, HCl, PM, and CO, which are continuously monitored, the heavy metals (HM) and dioxins emissions are not required to be monitored continuously; and few plants report them to the provincial "supervisory emission monitoring system (SEMS)" 11 . In 2020, more than 400,000 data on nine pollutants were collected based on CEMS (continuous emissions monitoring system) and SEMS nationwide.…”
Section: Emission Factorsmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment analyzed data from more than 400 factories in China and found that environmental footprint had a significant negative correlation with social economy. The constructed model could be used to effectively monitor urban exhaust gas emissions, with monitoring errors ranging from 0.003 to 0.09 [ 9 ].…”
Section: Introductionmentioning
confidence: 99%